English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

does anyone know how to fully prove the golden ratio. i've been to tons of sites and they all seem to skip some steps i need. i know that a+b/a = a/b and that eventually it comes out to 1+sqrt[5]/2 but how do you get to that?

2006-11-11 07:50:27 · 8 answers · asked by Bill s 2 in Science & Mathematics Mathematics

how does everyone keep getting sqrt[5]?
i've tried wiki's way a couple of times and i end up at the quadratic part and get stumped.

2006-11-11 08:08:07 · update #1

The expression is actually (a + b) /a = a / b,
not forgetting the brackets.
This gives : 1 + b / a = a / b

'b' is usually given the value of 1.
So, 1 + b / a = a / b becomes 1 + 1 / a = a

Now multiply through by a to get : a + 1 = a^2.
Rearranging gives : a^2 - a - 1 = 0

This is a quadratic equation, which can be
solved by using the quadratic formula.

Thus, a = {1 ± sqrt[1^2 - 4(1)(-1)]} / (2*1)
right here is where i get screwed up in this problem
by the way he set this up for the quadratic equation, a=a, b=a, c=1
where does he get "1" for the [-b] in the quadratic equation?, shouldn't it be set up
a = {a ± sqrt[-a^2 - 4(a)(-1)]} / (2*a)?

2006-11-11 08:42:08 · update #2

8 answers

The expression is actually (a + b) /a = a / b,
not forgetting the brackets.
This gives : 1 + b / a = a / b

'b' is usually given the value of 1.
So, 1 + b / a = a / b becomes 1 + 1 / a = a

Now multiply through by a to get : a + 1 = a^2.
Rearranging gives : a^2 - a - 1 = 0

This is a quadratic equation, which can be
solved by using the quadratic formula.

Thus, a = {1 ± sqrt[1^2 - 4(1)(-1)]} / (2*1)

= [1 ± sqrt(5)] / 2

The larger value, [1 + sqrt(5)] / 2,
not forgetting the brackets again,
is usually given as the value of the golden ratio.

2006-11-11 08:21:51 · answer #1 · answered by falzoon 7 · 1 0

(a+b)/a = a/b
(a/b + b/b)/(a/b)=a/b
(a/b + 1)/(a/b)=a/b
a/b+1 = (a/b)²
(a/b)² - a/b = 1
(a/b)² - a/b + 1/4 = 5/4
(a/b - 1/2)² = 5/4
a/b - 1/2 = √5/2
a/b = (1+√5)/2

Edit (for completeness): Note that the last steps could have also gone:
a/b - 1/2 = -√5/2
a/b = (1-√5)/2

However, while this solution satisfies the equation, the golden ratio is a ratio of lengths, which are always positive, so φ must also be positive. Since this solution is negative, it is not considered to be the golden ratio.

Edit 2: "how does everyone keep getting sqrt[5]"

From taking the square root of both sides in the third to last step.

Edit 3: No, the quadratic formula uses the coefficients of the variables, not the variuables themselves. In the equation a²-a-1=0
The coefficients are 1, -1, and -1, respectively. Perhaps you will be less confused if you relabel the free variable:

x²-x-1=0

x=(-1±√5)/1

Now are you less confused?

2006-11-11 08:00:34 · answer #2 · answered by Pascal 7 · 0 0

Yes. If you define it as the
- it is the limiting ratio of successive terms in the Fibonacci series
- you can define it directly, geometrically by 1 + 1/r = r

Either way you get the difference equation:
1 + 1/r = r
which gives you the quadratic:
r^2 -r -1 = 0
which has two roots: (1+√5) / 2 ~= 1.618 (Golden Mean),
(1-√5) / 2 ~= -0.618 = 1 - 1/r1 (conjugate GM)

Here's the derivation from Fibonacci series:
F(n) = x^n + y^n
y<0, so for large n, F(n) ~= x^n
F(n+1) ~= x^(n+1)
F(n+2) ~= x^(n+2) = F(n+1) + F(n)
Therefore x^(n+2) = x^(n+1) + x^n
x^2 = x + 1 , giving same quadratic as before.
r = Lim n->inf F(n+1)/F(n) or also Lim n->inf F(n)^(1/n)

2006-11-11 07:52:46 · answer #3 · answered by smci 7 · 0 0

The golden ratio is oftentimes referred to as the divine ratio, because it is likewise the ratio of stability. while you're making a cellular, you will use the golden ratio to verify the place to place the subsequent point, etc. So, if this is the ratio of stability, the two bodily and artistically, i could desire to verify the place superstitious minds could see it as some thing religious or perhaps godlike. only like casting out 9s.

2016-12-28 18:56:38 · answer #4 · answered by rankins 3 · 0 0

I believe your starting point is wrong, it should be:

1+b/a=a/b

the solution starts with a=Rb where R is the ratio.

putting it in the equation above you get

(R+1)/R=R,

R^2-R-1=0

and solving the quadratic equation you get

(1+sqrt(5))/2, not 1+(sqrt(5)/2)

2006-11-11 07:59:03 · answer #5 · answered by Grelann 2 · 1 0

Draw a perfect pentagram (5-point star).

You will find the Golden Ratio consistent in incredible ways throughout.

You will discover uniquely consistent trigonometrics within 54 & 108 degrees, as well as the contained pentagon.

2006-11-11 08:19:25 · answer #6 · answered by warmspirited 3 · 0 0

I'd do it dierecty, but Y!A wouldn't be too readable.

2006-11-11 07:53:44 · answer #7 · answered by novangelis 7 · 0 0

let f=golden ratio.
1/f-1=f
1-f=f^2
f^2+f-1=0
f=(-1+/-√(1^2-4*1*(-1)))/2
f=(-1+/-√(1+4))/2
f=(-1+√5)/2
f=(-1-√5)/2
f=(-1-√5)/2=-1.6180339887498948482045868343656
f=(-1+√5)/2=0.61803398874989484820458683436564

2006-11-11 10:03:05 · answer #8 · answered by yupchagee 7 · 0 0

fedest.com, questions and answers